1 ! + 2 ! + 3 ! 1 ⋅ 2 ⋅ 3 + 2 ! + 3 ! + 4 ! 2 ⋅ 3 ⋅ 4 + 3 ! + 4 ! + 5 ! 3 ⋅ 4 ⋅ 5 + ⋯ = ?
Notation
:
!
denotes the
factorial
notation. For example,
8
!
=
1
×
2
×
3
×
⋯
×
8
.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Brilliant solution. Sir, your solutions always inspire me to do more. I just wanted to ask how did you got − 2 after integration by putting x = 0 ? @Chew-Seong Cheong
Log in to reply
Thanks for liking my solutions. I have added a note to explain it.
Log in to reply
Is there any particular reason for choosing x = 0 for substitution?
Log in to reply
@Akshay Yadav – There is one mistake in the solution,
n = 0 ∑ ∞ n ! x n = e x instead of what is mentioned in the solution.
@Akshay Yadav – It is the easiest way to solve for c . Well you can use x = 1 or any other value.
Let us denote the general term by T n .
Then we have
T n = n ( n + 1 ) / n ! ( n + 2 ) .
Adding and removing 2 from numerator ,
T n = n − 1 / n ! + 2 / n ! ( n + 2 ) .
Therefore we generate last expression before telescoping.
T n = ( 1 / ( n − 1 ) ! − 1 / n ! ) + 2 ( 1 / ( n + 1 ) ! − 1 / ( n + 2 ) ! )
Thus after taking sum from n = 1 to ∞ Answer is 2
Problem Loading...
Note Loading...
Set Loading...
S = 1 ! + 2 ! + 3 ! 1 ⋅ 2 ⋅ 3 + 2 ! + 3 ! + 4 ! 2 ⋅ 3 ⋅ 4 + 3 ! + 4 ! + 5 ! 3 ⋅ 4 ⋅ 5 + ⋯ = n = 1 ∑ ∞ n ! + ( n + 1 ) ! + ( n + 2 ) ! n ( n + 1 ) ( n + 2 ) = n = 1 ∑ ∞ n ! ( n + 2 ) 2 n ( n + 1 ) ( n + 2 ) = n = 1 ∑ ∞ ( n + 2 ) ( n − 1 ) ! n + 1 = n = 0 ∑ ∞ ( n + 3 ) n ! n + 2
Now consider the Maclaurin series of e x ,
n = 0 ∑ ∞ n ! x n n = 0 ∑ ∞ n ! x n + 2 n = 0 ∑ ∞ ( n + 3 ) n ! x n + 3 n = 0 ∑ ∞ ( n + 3 ) n ! x n + 2 n = 0 ∑ ∞ ( n + 3 ) n ! ( n + 2 ) x n + 1 n = 0 ∑ ∞ ( n + 3 ) n ! n + 2 ⟹ S = e x = x 2 e x Integrate both sides = x 2 e x − 2 x e x + 2 e x − 2 Get from putting x = 0 , see Note ; × x 1 both sides = x e x − 2 e x + x 2 e x − x 2 Differentiate both sides = e x + x e x − 2 e x + x 2 e x − x 2 2 e x + x 2 2 Putting x = 1 = e + e − 2 e + 2 e − 2 e + 2 = 2
Note:
\begin{aligned} \sum_{n=0}^\infty \frac{x^{n+3}}{(n+3)n!} & = x^2e^x - 2xe^x + 2e^x + \color{#D61F06}{c} \quad \quad \small \color{#D61F06}{c \text{ is the constant of integration; by putting }x=0,} \\ \implies \sum_{n=0}^\infty \frac{\color{#D61F06}{0} ^{n+3}}{(n+3)n!} & = \color{#D61F06}{0}^2e^\color{#D61F06}{0} - 2(\color{#D61F06}{0})e^\color{#D61F06}{0} + 2e^\color{#D61F06}{0} + \color{#D61F06}{c} \\ 0 & = 2 + \color{#D61F06}{c} \\ \implies \color{#D61F06}{c} & = \color{#D61F06}{-2} \end{aligned}